Polyphenolic Compounds Inhibit Osteoclast Differentiation While Reducing Autophagy through Limiting ROS and the Mitochondrial Membrane Potential - Dipranjan Laha; Jaganmay Sarkar; Jyotirindra Maity; Asmita Pramanik; Md Sariful Islam Howlader; Derek Barthels; Hiranmoy Das (Biomolecules, 2022)
Polyphenolic compounds are a diverse group of natural compounds that interact with various cellular proteins responsible for cell survival, differentiation, and apoptosis. However, it is yet to be established how these compounds interact in myeloid cells during their differentiation and the molecular and intracellular mechanisms involved. Osteoclasts are multinucleated cells that originate from myeloid cells. They resorb cartilage and bone, maintain bone homeostasis, and can cause pathogenesis. Autophagy is a cellular mechanism that is responsible for the degradation of damaged proteins and organelles within cells and helps maintain intracellular homeostasis. Imbalances in autophagy cause various pathological disorders. The current study investigated the role of several polyphenolic compounds, including tannic acid (TA), gallic acid (GA), and ellagic acid (EA) in the regulation of osteoclast differentiation of myeloid cells. We demonstrated that polyphenolic compounds inhibit osteoclast differentiation in a dose-dependent manner. Quantitative real-time PCR, immunocytochemistry, and western blotting revealed that osteoclast markers, such as NFATc1, Cathepsin K, and TRAP were inhibited after the addition of polyphenolic compounds during osteoclast differentiation. In our investigation into the molecular mechanisms, we found that the addition of polyphenolic compounds reduced the number of autophagic vesicles and the levels of LC3B, BECN1, ATG5, and ATG7 molecules through the inactivation of Akt, thus inhibiting the autophagy process. In addition, we found that by decreasing intracellular calcium and decreasing ROS levels, along with decreasing mitochondrial membrane potential, polyphenolic compounds inhibit osteoclast differentiation. Together, this study provides evidence that polyphenolic compounds inhibit osteoclast differentiation by reducing ROS production, autophagy, intracellular Ca2+ level, and mitochondrial membrane potentials.